The The Correlation Between Ice Breaking Strategy And Students’ Motivation In Learning English At Tenth Grade MA Hubbulwathan Duri - Rasyid Pane, Mhd. Arfandhi (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2024)
This research was a quantitative research. The subjects of this research were the tenth grade students of MA Hubbulwathan. The sampling technique used purposive sampling. The sample studied amounted to 36 respondents, the data collection technique in this study used a questionnaire. The data analysis method used the correlation method analysis with the help of IBM SPSS Statistics Version 22 software. Before analyzing the data, validity and reliability tests are carried out first. The results of the correlation test show a correlation value of 0.643, which means that there is a strong relationship between the ice breaking strategy and the learning motivation of tenth grade students at MA Hubbulwathan Duri. It can be concluded that Ha is accepted and Ho is rejected.